Effective Antitumor Synergistic Treatment with Fiber-Photothermal Therapy and Heat Shock Protein Inhibitors - Zhang, Zhuo; Yue, Xu; Lan, Ni; Zhang, Yongkang; Li, Zesen; Jin, Fangzhou; Wang, Yifei; Guan, Bai-Ou; Ran, Yang; Liu, Kaisheng (ACS applied materials & interfaces, 2025)
Effective treatment of malignant tumors remains a thorny issue in current medicine. As a new type of anticancer strategy, photothermal therapy (PTT) has attracted tremendous attention due to its favorable therapeutic effectiveness, high spatial-temporal controllability, and low occurrence of side effects. However, the efficacy of PTT is significantly reduced due to the limited penetration of light and heat-induced overexpression of heat shock protein (Hsp). Herein, we propose an antitumor synergistic therapy that combines fiber-optic PTT and Hsp inhibitors. A rare-earth-doped optical fiber was used as the PTT actuator, and the Hsp inhibitor AT533 was loaded on the fiber surface by use of a hydrogel layer. PTT fibers can be guided to reach tumor lesions directly without being subject to the light penetration limit. The Hsp inhibitor can be released upon the softening of the hydrogel layer under photoheating to deactivate Hsp in the tumor and thus reduce the resistance of the tumor to PTT. This synergistic treatment enhanced the effect of PTT and successfully eradicated tumors in colorectal cancer (CRC) xenograft mouse models, providing a feasible way to realize antitumor and antirecurrence treatment. More importantly, the success of the synergistic treatment of PTT and Hsp inhibition opens new avenues for the development of multimodal and multitype synergistic fiber-optic treatments, which offer pronounced enhancement of therapeutic effectiveness for treating cancer.